Effect of traditional roughage-based or limit-fed, high-energy diets on growth performance and digestion in newly received growing cattle and subsequent implications on feedlot growth performance and carcass characteristics and effect of Enogen corn hybrids or conventional hybrids in diets containing corn coproducts on performance and digestion in newly received growing cattle - Scilacci, Morgan A. (Kansas State University, 2021)
Two performance studies and one digestibility trial were conducted to determine the effect of traditional roughage-based diets or limit-fed, high-energy diets on growth performance, behavior, health, and digestion in newly received growing cattle and subsequent implications on feedlot growth performance and carcass characteristics. 40% of diet DM was based on Sweet Bran [proprietary wet corn gluten feed (WCGF); Cargill Animal Nutrition, Blair, NE]. In Exp. 1, 409 crossbred heifers (initial BW = 279 ± 24 kg) were used in a randomized complete block design and assigned to 1 of 2 dietary treatments: 0.99 megacalories of net energy for gain per kilogram of dry matter (Mcal NEg/kg DM) fed for ad libitum intakes (0.99AL; n = 205) or 1.32 Mcal NEg/kg DM limit-fed at 85% of 0.99AL intakes (1.32LF85%; n = 204). In Exp. 2, 370 crossbred heifers (initial BW = 225 ± 20 kg) were used in a randomized complete block design and fed the same diets from Exp. 1, but the 1.32LF treatment was limit-fed at 2.2% of body weight (BW) daily on a DM basis (1.32LF2.2). In Exp. 3, eight ruminally-cannulated crossbred Angus heifers (initial BW = 204 ± 11 kg) in a cross-over design were fed diets from Exp. 1 in a 2-period digestibility study. Gain:feed efficiency (G:F) was greater (P < 0.01) by 47% and 35% in Exp. 1 and 2 for 1.32LF85% and 1.32LF2.2 heifers compared to 0.99AL heifers, respectively. For 1.32LF85% heifers ADG was greater and DMI was lower in Exp. 1; ADG was lower for 1.32LF2.2 heifers in Exp. 2 than 0.99AL heifers (P < 0.01). Rumination time was greater (P < 0.01) for 0.99AL heifers compared to 1.32LF85% in Exp. 1 and 1.32LF2.2 heifers in Exp. 2. Activity was greater (P < 0.01) for 1.32LF2.2 heifers compared to 0.99AL heifers in Exp. 2. 6.9% more light-sort carcasses than heavy-sort carcasses had livers with large, active abscesses (P = 0.03) in Exp. 1. Feedlot morbidity was not different between backgrounding diets in Exp. 1, but morbidity was 15.5% greater for 1.32LF2.2 cattle compared to 0.99AL cattle in Exp. 2. A significant interaction between backgrounding diet and sort group occurred, because liver scars were greater (P < 0.04) for 1.32LF85% carcasses in the heavy-sort group than 1.32LF carcasses in the light-sort group. Light-sort groups had fewer (P < 0.01) edible livers than heavy-sort groups, suggesting that greater number of days on feed increases the risk of liver abscess prevalence and condemnation to occur in light-sort cattle. Apparent total-tract DM and OM digestibility was greater for 1.32LF85% diets than for 0.99AL diets in Exp. 3 (P < 0.01), but fiber digestibility was not different (P ≥ 0.59). Limit-fed, high-energy diets fed during the growing phase had little carryover effect on feedlot growth performance or carcass characteristics. In addition, one performance study and one digestibility trial were conducted to evaluate the effect of feeding corn grain and corn silage from Enogen corn hybrids (EC; Syngenta Seeds, LLC., Downers Grove, IL) or conventional corn hybrids (CON) in diets containing either wet distillers grain (WDG; ICM Biofuels, St. Joseph, MO) or Sweet Bran [proprietary wet corn gluten feed (WCGF); Cargill Animal Nutrition, Blair, NE]. Experimental unit was pen. In Exp. 1, 384 crossbred heifers (initial BW = 264 ± 19.1 kg) were used in a completely randomized design, 81-d receiving and growing study, with a 2 x 2 factorial arrangement of 4 dietary treatments. There were 8 pens per treatment, with 12 heifers stratified by weight to each pen. Experimental diets were formulated to contain 30% WDG or 30% WCGF on a dry matter (DM) basis and provide 1.12 Mcal of NEg/kg DM. All diets were fed once daily for ad libitum consumption. In Exp. 2, eight ruminally cannulated crossbred heifers (initial BW = 370 ± 42.6 kg) were used concurrently with Exp. 1 to evaluate intake and digestibility of dietary treatments from Exp. 1 in a replicated 4 × 4 Latin square design. Four consecutive, 15-d periods consisted of 10 d for diet adaptation, 4 d of fecal sampling, and 1 d of ruminal sampling; experimental unit was animal. In Exp. 1, no corn source x coproduct interactions were observed (P > 0.10) for performance or fecal starch analysis, with the exception of dry matter intake (DMI; P < 0.01) and G:F (P = 0.01) at day 14. An effect of coproduct was observed at day 64, with heifers fed WDG having greater ADG than heifers fed WCGF (P < 0.03). Effect of coproduct on DMI or gain:feed (G:F) was not significantly different after day 14 (P > 0.05). Heifers fed EC had greater ADG at days 28 and 56 (P < 0.01) than heifers fed CON, but G:F was not different between corn sources after day 28 (P > 0.13). Starch concentration of fecal DM was greater in CON heifers than EC heifers (P < 0.02). In Exp. 2, corn source × coproduct interactions were not observed (P > 0.16). A main effect of coproduct occurred for molar percentage of isobutyrate (P < 0.05), and there was a tendency for greater digestibility of starch in EC diets than CON diets (P < 0.07), but neither DM nor fiber digestibility was affected by corn source or coproduct (P > 0.34). Results indicate EC when fed with WCGF or WDG did not enhance growth performance of growing cattle, possibly due to similar dietary net energy densities fed in all diets.
Keywords: Limit feeding; Liver abscesses; Growing cattle; Coproduct; Amylase enzyme; Corn silage